2013
DOI: 10.1021/ol402318m
|View full text |Cite
|
Sign up to set email alerts
|

Laevinoids A and B: Two Diterpenoids with an Unprecedented Backbone from Croton laevigatus

Abstract: Chemical fractionation of the ethanolic extract of a Chinese herbal plant, Croton laevigatus, yielded laevinoids A (1) and B (2) with a new rearranged ent-clerodane scaffold named as laevinane. The structures of 1 and 2 were assigned on the basis of detailed spectroscopic analyses with their absolute configurations being established via single-crystal X-ray diffraction studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…The 1 H-1 H COSY experiment showed connectivity of three moieties: I: 1 CH 2 -2 CH 2 -3 CH 2 ; II: 5 CH-6 CH 2 -7 CH 2 ; and III: 9 CH-11 CH(O)-12 CH 2 . The HMBC correlations from CH 3 -19 (d H 0.79, 3H, s) to C-3 (d C 35.1), C-5 (d C 44.4), and C- 18 (d C 15.7); from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]each 1H,d,J ¼ 11.2 Hz) to C-3, C-5, and C-19 (d C 17.7); and from H 2 -2 (d H 1.50 and 1.60, each 1H, m) to C-4 (d C 37.5) indicated that C-4 connected units I and II together. The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 H-1 H COSY experiment showed connectivity of three moieties: I: 1 CH 2 -2 CH 2 -3 CH 2 ; II: 5 CH-6 CH 2 -7 CH 2 ; and III: 9 CH-11 CH(O)-12 CH 2 . The HMBC correlations from CH 3 -19 (d H 0.79, 3H, s) to C-3 (d C 35.1), C-5 (d C 44.4), and C- 18 (d C 15.7); from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]each 1H,d,J ¼ 11.2 Hz) to C-3, C-5, and C-19 (d C 17.7); and from H 2 -2 (d H 1.50 and 1.60, each 1H, m) to C-4 (d C 37.5) indicated that C-4 connected units I and II together. The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together.…”
Section: Resultsmentioning
confidence: 99%
“…The HMBC correlations from CH 3 -20 (d H 0.96, 3H, s) to C-1 (d C 41.4), C-5, and C-9 (d C 66.0) and from H 2 -1b (d H 0.96, 1H, m) to C-9 suggested that C-10 (d C 35.9) connected units I and III together. Furthermore, the HMBC correlations from H-9 (d H 1.57, 1H, d, J ¼ 2.0 Hz) to C- 17 (d C 78.5),1H,td,J ¼ 5.2,2.4 Hz) and H 2 -6 (d H 1.32 and 1.60, each 1H, m) to C-8 (d C 80.1), and from H [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]each 1H,d,J ¼ 9.6 Hz) to C-7 (d C 33.3), C-9, IR spectrum showed absorption bands for hydroxyl (3422 cm À1 ), ester carbonyl (1735 cm À1 ) and olen (1676 cm À1 ) functionalities. The 1 H and 13 C NMR spectroscopic data (Tables 1 and 2) of 3 resembled those of 1 and 2, sharing the same AB rings, and also belongs to nor-labdane-type diterpene series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bafoudiosbulbin B (181), isolated from Dioscorea bulbifera, composed of three lactone rings, and the structure was corrected by chemical transformation (Teponno et al 2008). Laevinoids A and B (182 and 183) isolated from Croton laevigatus (Wang et al 2013a), and blepharolide A (184) isolated from Salvia blepharophylla (Bisio et al 1999), were assigned with an unusual clerodane skeleton containing a cyclopropane ring. Three compounds from Salvia species, 2a-hydroxy-7-epi-8b,17-dihydrolanguiduline (185) (Sanchez et al 1995), salvigenolide (186) (Esquivel et al 1985) and dugesin A (187) (Xu et al 2004), compose of a seven-membered ring B, which is uncommon in clerodane-type diterpenoids.…”
Section: Type Icmentioning
confidence: 99%
“…6 The genus Croton (Euphorbiaceae) has been reported to be another rich source of clerodane diterpenoids, 1 which is still of interest to natural product scientists. 7,8 Croton euryphyllus W. W. Smith is a shrub widely distributed in southwest China especially in the Karst region of Guangxi Province, 9 and its roots have been used as a traditional medicine for the treatment of rheumatism, traumatic injury, and related diseases. 10 The phytochemical constituents of Croton euryphyllus had never been investigated unless our recent report on the volatile constituents of this plant.…”
Section: Introductionmentioning
confidence: 99%